SELF-REGULATED EFL SPEAKERS THROUGH METACOGNITIVE INSTRUCTION - Syam, Ulfah; Sahib, Nurfaizah; Rampeng, Rampeng (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This qualitative study investigates the role of metacognitive instruction in developing self-regulated English as a Foreign Language (EFL) speaking skills among undergraduate students. Speaking is often perceived as one of the most challenging language skills due to its cognitive complexity and affective demands. Drawing on theories of metacognition and self-regulated learning, this study explores how metacognitive instruction is implemented in EFL speaking classrooms, how it fosters students’ self-awareness, and how it contributes to the development of self-regulation in speaking. Data were collected through classroom observations, semi-structured interviews, and analysis of instructional materials at State University of Makassar. The data were analyzed thematically using systematic coding and categorization procedures. The findings reveal that metacognitive instruction was implemented through structured pre-speaking, while-speaking, and post-speaking stages that explicitly emphasized planning, monitoring, and evaluation. The instruction enhanced students’ linguistic and affective self-awareness and supported the gradual development of self-regulated speaking behaviors, including independent monitoring, self-correction, and motivational regulation. The study highlights the pedagogical value of integrating metacognitive instruction into EFL speaking classrooms to promote learner autonomy, confidence, and sustainable speaking development